FAKTOR-FAKTOR PENYEBAB PERBEDAAN PENGHITUNGAN KERUGIAN KEUANGAN NEGARA DALAM TINDAK PIDANA KORUPSI (Kasus Korupsi Dana Hibah Persiba Bantul) - Masdar Ryketeng (YUME : Journal of Management, 2020)
The Inspectorate of Bantul District, and the Yogyakarta District Court) in the corruption case of Persiba Bantul grants. The calculation of the two government audit agencies was significantly lower than the amount settled by the court. There was also a different amount resulted from the calculation between BPKP and the inspectorate. These differences may affect public trust on government audit agencies in supporting corruption eradication. This study used a qualitative method with a case study approach.  The results show that there are differences in calculating the state financial loss due to two factors: components of the calculation and recognition of amounts of the loss by BPKP and the inspectorate. Specificially, differences are due to access to audit evidences and new facts, assigned time of auditors, and human factor. The court seems to have advantages regarding to access audit evidence and other information and therefore, the court could set a higher amount of the state loss. This study contributes to having better understanding of calculating the state financial loss.  Keywords: counting losses to the country, corruption case, losses to the country, thematic analysis